Effect of boundary layers on reverse osmosis through a horizontal membrane - Kargol, A (Elsevier Science Bv, 1999)
This work is concerned with the reverse osmosis through a horizontal membrane, generated by an external pressure. A boundary layer, unstable in gravitational field, forms on the membrane. Assuming constant thickness of the boundary layer in a stationary state, we obtain equations for the concentration of the filtrate and of the solution inside the layer. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: reverse osmosis; membrane transport; flux; boundary layer